Lipocalin-2 Serum Levels in Rheumatoid Arthritis Patients Treated with Adalimumab and Its Correlation with Proinflammatory Factors - Javier Conde-Aranda; Morena Scotece; María Varela-García; Carlos Torrijos-Pulpón; Laura Arosa; Miguel Camba-Gómez; Jesús Pino; Oreste Gualillo (Wiley, 2024)
Background. Obesity is associated with an increased risk for different chronic diseases such as osteoarthritis (OA) or rheumatoid arthritis (RA). In fact, adipose tissue is now recognized as an endocrine organ able to secrete a wide variety of factors called adipokines, which have been demonstrated to participate in the pathophysiology of RA by regulating inflammation and immunity. LCN2 is one of these adipose tissue-derived factors. However, scarce information is available about the levels of this adipokine in different rheumatic diseases. Therefore, we aimed to analyze LCN2 serum levels in healthy, OA, and RA patients under different treatments. Methods. Serum levels of LCN2, among other proinflammatory and chemotactic factors, have been measured by ELISA or Multiplex in the following four groups of individuals: healthy, OA, and RA patients treated with conventional treatment or adalimumab. Results. We found increased serum levels of LCN2 in OA and RA patients. Interestingly, LCN2 serum levels show a similar pattern to that observed for different proinflammatory and chemotactic factors, being increased in RA conventional treated patients in comparison to RA patients treated with adalimumab. Also, RA patients under conventional treatment revealed a positive and significant correlation between LCN2 and CCL2, CCL3, IL-8, IL-1β, IL-6, and CRP. In patients with RA treated with adalimumab, only IL-6 and CRP correlated significantly with LCN2. Conclusions. Our results clearly suggest that LCN2 is modulated and associated with inflammation in rheumatic diseases. Therefore, the serum levels of this adipokine might be used as an additional biomarker of the inflammatory/disease activity.